A checklist of chiggers from Brazil, including new records (Acari: Trombidiformes: Trombiculidae and leeuwenhoekiidae) - Jacinavicius, Fernando de Castro; Bassini-Silva, Ricardo; Mendoza-Roldan, Jairo Alfonso; Pepato, Almir Rogério; Ochoa, Ronald; Welbourn, Cal; Barros-Battesti, Darci Moraes [UNESP] (Pensoft Publishers, 2018)
A checklist of the family Trombiculidae and Leeuwenhoekiidae is presented, containing 63 species in 30 genera of chiggers from 80 different hosts and 146 localities in Brazil. The type locality and depository are provided, including new locality and host records for the country.
Keywords: Brazil; Chigger mites; Cricetidae; Didelphidae; Distribution